Integrating Multiliteracies for Preservice Teachers Using Project-Based Learning - Terry Sefton; Kara Smith; Wayne Tousignant (University of Windsor, 2020)
Using a project-based learning approach, three teacher educators, teaching three different methodology courses, worked together to create, plan, and assess an arts-based assignment completed by preservice candidates. The preservice teachers created an animation project while applying curriculum expectations in three subject areas: visual arts, music, and language arts. The three subjects were segregated for the purpose of instruction, integrated during the group work and creative process, and then jointly assessed using negotiated reporting. This paper describes the project and details the challenges of integrating teaching and learning across institutionally segregated courses when student expectations are conditioned by their prior experience of siloed, subject-based learning, and discusses lessons learned by the three teacher educators and implications for team teaching across the curriculum.